Detailed Anatomical Analysis of the Sphenoid Sinus and Sphenoid Sinus Ostium by Cone-Beam Computed Tomography. Issue 6 (September 2016) - Yilmaz, Nesibe; Kose, Evren; Dedeoglu, Numan; Colak, Cemil; Ozbag, Davut; Durak, Mehmet Akif
Abstract : Abstract: The aim of this study is the evaluation of the anatomical structures of sphenoid sinus ostium used as a reference point for transsphenoidal surgery by cone beam computed tomography. The authors' study was performed using the cone-beam computed tomography images of 16 to 82-year old 200 (112 female, 88 male) patients (Newton 5G, Verona, Italy). Septum deviation of sphenoid sinus and the distance between 2 ostia were evaluated by coronal and axial sections, respectively. Pneumatization degree of sphenoid sinus, diameter of sphenoid sinus ostium, and distance lower edge of superior turbinate to sphenoid sinus ostium were measured by using sagittal sections. The sellar type was the most common pneumatization type of sphenoid sinus in authors' study. While the C-type septum deviation was observed as the most common, T-type deviation was the least type. Sphenoid sinus ostium was bilaterally in 71.5% of individuals, and it was not found in 10% of individuals included in the study. A significant decrease was determined in diameter of the left sphenoid sinus ostium with aging. The distances between 2 sphenoid sinus ostia were 7.30 ± 2.77 mm for women and 6.09 ± 2.58 mm for men, respectively. No statistical differences were found in women and men in terms of distances between the lower edge of the right and left superior turbinate and sphenoid sinus ostium on their sides. Consequently, making detailed preoperative radiological evaluation of anatomic variations of sphenoid sinus and sphenoid sinus ostium is important in terms of guiding the surgeon in the process of a successful transsphenoidal surgery.